Electronic and optical properties of the exponential and hyperbolic Rosen–Morse types quantum wells under applied magnetic field (2023)
ABSTRACT: In this study, we considered the electronic and optical properties of quantum wells with the exponential and hyperbolic Rosen–Morse potentials under an applied magnetic field. Calculations are made within the framework of effective mass and parabolic band approximations. We have used the diagonalization method by choosing a wave function based on the trigonometric orthonormal function to find eigenvalues and eigenfunctions of the confined electron. Our results show that the magnetic field, asymmetry, and confinement parameters cause a significant increase in electron energies and energy differences between the electron states and the blue shift in the absorption peaks. These results can be used to probe materials’ electronic and structural properties and develop new materials with tailored optical properties.